Does vitamin D deficiency increase orthostatic hypotension risk in the elderly patients? - Soysal, PINAR; SOYSAL, PINAR; YAY, Adnan; Isik, Ahmet Turan (My University, 2014)
Orthostatic hypotension (OH) is closely associated with falls, cardiovascular events and mortality in the elderly patients. The aim of the study is to evaluate the OH prevalence among patients over the age of 65 years, to find out the impact of this condition on daily living activities, and to determine the possible effects of vitamin D levels on OH in elderly patients. Eight hundred and forty nine geriatric patients who had undergone comprehensive geriatric assessment were retrospectively evaluated and 546 patients were included in the study. The patient-s demographic characteristics, blood pressures, comorbid diseases, polypharmacy status, cognitive and nutritional states, basic and instrumental daily living activity indexes and laboratory values were obtained from hospital files. Serum 25-hydroxyvitamin D [25(OH)D] was measured by radioimmunoassay. The prevalence of OH was found to be 27.5%. Both daily living activity indexes were significantly lower in older patients with OH (p < 0.02), and serum 25(OH)D levels were significantly lower in older patients with OH (p < 0.01). Our findings suggest that vitamin D deficiency may be a factor in OH development. Because this condition is also preventable and correctable, serum vitamin D levels should be checked during the evaluation of OH patients and any detected deficiency should be treated accordingly. (C) 2014 Elsevier Ireland Ltd. All rights reserved.